1984
DOI: 10.1152/ajpendo.1984.246.6.e476
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced muscle glucose metabolism after exercise: modulation by local factors

Abstract: Studies in the rat suggest that after voluntary exercise there are two phases of glycogen repletion in skeletal muscle (preceding study). In phase I glucose utilization and glycogen synthesis are enhanced both in the presence and absence of insulin, whereas in phase II only the increase in the presence of insulin is found. To determine whether these alterations and in particular those mediated by insulin are due to local or systemic factors, one hindlimb of an anesthetized rat was electrically stimulated, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
135
1
8

Year Published

1996
1996
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(147 citation statements)
references
References 16 publications
3
135
1
8
Order By: Relevance
“…14 CO 2 production from [U- 14 C]glucose mainly reflects CO 2 derived from the decarboxylation of glucose in the pentose phosphate pathway and in the pyruvate dehydrogenase step in the pathway of fatty acid synthesis. Because lipid synthesis was stimulated in these cells, we used [6][7][8][9][10][11][12][13][14] C]glucose to determine whether the overexpression of myophosphorylase also stimulated glucose oxidation. We found that there was no difference in the Glucose Uptake and Phosphorylation-The effect of phosphorylase dosage on the uptake and phosphorylation of the nonmetabolizable glucose analogue 2-deoxyglucose was studied (Table III).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…14 CO 2 production from [U- 14 C]glucose mainly reflects CO 2 derived from the decarboxylation of glucose in the pentose phosphate pathway and in the pyruvate dehydrogenase step in the pathway of fatty acid synthesis. Because lipid synthesis was stimulated in these cells, we used [6][7][8][9][10][11][12][13][14] C]glucose to determine whether the overexpression of myophosphorylase also stimulated glucose oxidation. We found that there was no difference in the Glucose Uptake and Phosphorylation-The effect of phosphorylase dosage on the uptake and phosphorylation of the nonmetabolizable glucose analogue 2-deoxyglucose was studied (Table III).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, it has been shown that insulin is not required to mediate glucose uptake during contractions (3,4) and that contractile activity augments glucose uptake by muscle even in severely insulin-deficient diabetic rats (5). Furthermore, in exercised muscle, glucose uptake and disposal are enhanced independently of insulin (6). Insulin sensitivity of glucose uptake and glycogen synthesis are increased in exercised muscle, in normal humans and insulin-deficient type I diabetic patients (7,8).…”
mentioning
confidence: 99%
“…Increased liver glycogen breakdown and plasma lactate levels have been observed after caffeine ingestion, [69,72,102,[105][106][107][108][109] and lactate is known to be a strong inhibitor of lipolysis. Thus caffeine might also exert depressing effects on FA oxidation in exercising muscle cells.…”
Section: Caffeine Ingestionmentioning
confidence: 99%
“…Intracellular glycogen plays a major role as a fuel for acute muscle contraction, and its concentration is dramatically reduced in response to a single bout of exercise (6,14,25,38). The facilitation of glycogen resynthesis after exercise causes a marked accumulation of glycogen, i.e., the well-known phenomenon of glycogen supercompensation.…”
mentioning
confidence: 99%